Analisis Evaluasi Penerimaan E-Learning Platform oleh Guru SMA dengan Model Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) - Tri Yudianto; Eko Indrajit; Amelia Makmur; Erick Dazki (Instructional Development Journal, 2024)
The aim of the research is to evaluate the Acceptance of the E-Learning Platform by High School Teachers using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) Model. This research uses explanatory quantitative methods. The population that has been determined in this research is all high school teachers in City X. The sample in this research consisted of 100 respondents. Researchers used accidental sampling technique, the type of data used in this research is primary data. The data collection technique was carried out using a questionnaire distributed via Google Form. The data analysis technique in this research uses Partial Least Square (PLS). The research results show that 1) Performance Expectancy has no effect on Use Behavior. 2) Performance Expectancy has no effect on Behavioral Intention. 3) Effort Expectancy has no effect on Use Behavior. 4) Effort Expectancy has a significant effect on Behavioral Intention. 5) Social Influence has no effect on Use Behavior. 6) Social Influence has no effect on Behavioral Intention. 7) Facilitating Conditions have a significant effect on Use Behavior. 8) Facilitating Conditions have a significant effect on Behavioral Intention. 9) Hedonic Motivation has no effect on Use Behavior. 10) Hedonic Motivation has no effect on Behavioral Intention. 11) Price Value has no effect on Use Behavior. 12) Price Value has no effect on Behavioral Intention. 13) Habit has a significant effect on Use Behavior. 14) Habit has no effect on Behavioral Intention. 15) Behavioral Intention has a significant effect on Use Behavior.